2009
DOI: 10.1113/jphysiol.2008.161331
|View full text |Cite
|
Sign up to set email alerts
|

The SNAT4 isoform of the system A amino acid transporter is functional in human placental microvillous plasma membrane

Abstract: Placental system A activity is important for the supply of neutral amino acids needed for fetal growth. There are three system A isoforms: SNAT1, SNAT2 and SNAT4, but the contribution of each to system A-mediated transport is unknown. Here, we have used immunohistochemistry to demonstrate that all three isoforms are present in the syncytiotrophoblast suggesting each plays a role in amino acid transport across the placenta. We next tested the hypothesis that the SNAT4 isoform is functional in microvillous plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 57 publications
7
57
0
Order By: Relevance
“…Immunohistochemical data confirmed that in human placentas, SNAT2 is expressed in the villous trophoblast, in both the syncytio-and cytotrophoblast (26). However, in IUGR placentas, SNAT2 staining intensity seemed to be lower in the syncytiotrophoblast.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Immunohistochemical data confirmed that in human placentas, SNAT2 is expressed in the villous trophoblast, in both the syncytio-and cytotrophoblast (26). However, in IUGR placentas, SNAT2 staining intensity seemed to be lower in the syncytiotrophoblast.…”
Section: Discussionsupporting
confidence: 65%
“…Finally, because the other SNAT gene isoforms (SNAT1 and SNAT4) may contribute to System A amino acid transporter activity in the human placental trophoblast (26), the analysis of their expression in this study population might clarify the role of System A amino acid transporter deregulation in the etiopathogenesis of intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…System A and system y + L are expressed at high levels in the placenta in the late stage of gestation. These results tend to be consistent with the previous studies [26,34,35]. Moreover, it has been reported that system A plays a key role in glutamine transport from the maternal side into placental cells [18,33].…”
Section: Discussionsupporting
confidence: 83%
“…However, little is known about the expression of nutrient transporters in the early period of gestation or their expression in cytotrophoblast cells [26]. …”
Section: Introductionmentioning
confidence: 99%
“…It is located in the syncytiotrophoblast and consists of three isoforms: SNAT1, SNAT2, SNAT4. The expression of these different isoforms changes in the human placenta during pregnancy (Desforges et al 2009). In vitro studies with human placental explants or trophoblast cells showed that SNAT proteins are upregulated by insulin, leptin and IGF-I and down-regulated by hypoxemia, nitric oxide and free oxygen radicals (Jones et al 2007).…”
Section: The Fetal Supply Linementioning
confidence: 97%